High-flame-retardant polyester fiber for protective gloves and preparation method of high-flame-retardant polyester fiber
Through the copolymerization of phosphorus-containing flame retardant and acidic silica and RAFT reagent grafting technology, the flame retardant and ultraviolet resistance of polyester fibers are enhanced, and the performance degradation of existing polyester fibers in high temperature and ultraviolet environments is solved. Achieve efficient protection effect.
Patent Information
- Application Number
- CN202411435979.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
AI Technical Summary
The existing polyester fiber has deteriorated flame retardant performance in high temperature, fire source and strong ultraviolet environments, and its UV resistance is limited, which affects its application in protective gloves.
The in-situ polymerization of phosphorus-containing flame retardant and acid silica is used to form a copolyester, and the flame retardant and ultraviolet resistance of the fiber is enhanced by grafting and photocatalyst.
It realizes the high flame retardancy and UV resistance of polyester fiber, extends its service life, provides reliable protection in harsh environments, and reduces safety hazards.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fibers, in particular to highly flame-retardant polyester fibers for protective gloves and a preparation method thereof. Background Art
[0002] Polyester fiber (polyester fiber) is widely used in textile, industrial protection and other fields due to its excellent mechanical properties, wear resistance and chemical stability. However, polyester fiber itself is flammable and easily burns and releases harmful gases when encountering a fire source, which limits its use in application scenarios that require flame retardant properties. In addition, polyester fiber will undergo photodegradation when exposed to ultraviolet light for a long time, resulting in reduced fiber strength, color discoloration and increased brittleness, which greatly shortens its service life. Ultraviolet aging not only affects the physical properties of the fiber, but also seriously weakens its flame retardant properties. The molecular chain breakage and oxidation reactions caused by ultraviolet radiation cause the added flame retardant to decompose or migrate, resulting in a weakening of the flame retardant effect, thereby increasing the flammability of the material. These problems are particularly prominent in applications such as protective gloves that are directly exposed to sunlight or outdoor environments.
[0003] Existing flame retardant technologies for polyester fibers are usually achieved by adding flame retardants to polyester or using blending modification. However, these methods are prone to failure of flame retardants under long-term ultraviolet irradiation, migration, decomposition and other phenomena, resulting in a significant decrease in the flame retardant properties of the fiber. In addition, the addition of flame retardants may also have an adverse effect on the mechanical properties of polyester fibers. On the other hand, in order to improve the anti-ultraviolet performance, ultraviolet absorbers or stabilizers are usually added to enhance the light resistance of the fiber, but the effect of such methods is often limited and they are prone to failure in high ultraviolet environments.
[0004] Therefore, developing a polyester fiber with both high flame retardancy and UV resistance is crucial to improving the safety protection capabilities of protective gloves in high temperature, fire and strong UV exposure environments. Developing polyester fibers with high flame retardancy and UV resistance can not only extend the service life of gloves and avoid the degradation of flame retardancy due to UV aging, but also provide reliable protection in harsh environments and reduce safety hazards. Summary of the invention
[0005] The object of the present invention is to provide a highly flame-retardant polyester fiber for protective gloves and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing highly flame-retardant polyester fiber for protective gloves: S1: adding a dicarboxylic acid flame retardant and ethylene glycol into a reaction container, stirring evenly, heating to 180-185° C. under a nitrogen atmosphere for reaction for 6-6.5 hours, further heating to 195° C., removing ethylene glycol and water, and obtaining a flame retardant diol compound;
[0008] Furthermore, in the preparation process of the dicarboxylic acid flame retardant diol compound, the volume ratio of dicarboxylic acid flame retardant: ethylene glycol is (0.8-1): (2-2.4);
[0009] Further, the dicarboxylic acid flame retardant includes [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid;
[0010] S2: Ethylene glycol, deionized water and phosphoric acid are added to the reaction container in sequence, the pH is adjusted to 2.0-2.1, tetraethyl orthosilicate is added, stirred evenly, silane coupling agent KH560 is added, the reaction is kept warm for 4-4.5 hours, and ethanol and water are removed by vacuum distillation to obtain nano-silica sol;
[0011] Furthermore, in the preparation process of the nano-silica sol, the volume ratio of phosphoric acid:ethyl orthosilicate:silane coupling agent KH560 is 1:100:1;
[0012] Furthermore, the substance used to adjust the pH includes phosphoric acid;
[0013] S3: Add terephthalic acid and ethylene glycol to a reaction vessel, preheat to 230°C for esterification reaction, add flame retardant diol compound, nano silica sol, and ethylene glycol antimony when the water content reaches the theoretical value, place the reaction system at 250-260°C and 300Pa vacuum, react for 60-65min, further heat to 270-275°C for reaction for 2-2.5h, place the reaction product at 120-140°C for pre-crystallization treatment, dry, and cool to room temperature to obtain polyester;
[0014] Furthermore, in the preparation process of the polyester, the molar ratio of terephthalic acid: ethylene glycol: flame retardant diol compound is (1.3-1.35): (0.05-0.1): 1; the amount of nano-silica sol added is 1-3wt% of the total mass of terephthalic acid, ethylene glycol, and flame retardant diol compound;
[0015] Furthermore, the pre-crystallization treatment time is 3-3.5h;
[0016] Furthermore, the polyester has a moisture content of ≤50ppm;
[0017] S4: spinning and drawing the polyester to obtain polyester fibers;
[0018] Further, the spinning parameters include a fiber plate size of 0.4 mm×36, a spinning rate of 600 m / min, and a spinning temperature of 260-290°C;
[0019] Further, the drawing parameters include a drawing hot plate A temperature of 160-165° C., a drawing hot plate B temperature of 80-85° C., and a drawing ratio of 3.5;
[0020] S5: placing the polyester fiber in a reaction container, adding an ethanol solution of catechol and a Tris buffer solution of branched polyethyleneimine, shaking and reacting at room temperature for 24 hours, taking out the polyester fiber, washing it alternately with deionized water and ethanol, and vacuum drying it at 60°C for 24 hours to obtain a modified polyester fiber;
[0021] Furthermore, in the preparation process of the modified polyester fiber, the volume ratio of the ethanol solution of catechol to the Tris buffer solution of branched polyethyleneimine is 1:(0.5-2);
[0022] Further, the concentration of the ethanol solution of catechol is 1 mg / mL;
[0023] Furthermore, the concentration of the Tris buffer solution of the branched polyethyleneimine is 0.5-2 mg / mL;
[0024] Furthermore, the concentration of the Tris buffer solution is 0.01 M, and the pH is adjusted to 8.5 using 0.01 M sodium hydroxide;
[0025] S6: Add RAFT agent, catalyst and dehydrating agent to N,N-dimethylformamide respectively, stir evenly to obtain solution A, solution B and solution C; add solution B and solution A to a reaction vessel, stir evenly, add modified polyester fiber, seal, vacuumize and nitrogen-fill three times, inject solution A into the reaction vessel, vacuumize and nitrogen-fill three times, heat to 40-42°C for reaction for 24h, take out the polyester fiber, wash alternately with N,N-dimethylformamide and ethanol, and vacuum dry at 50°C for 12h to obtain RAFT agent grafted polyester fiber;
[0026] Furthermore, in the preparation process of the RAFT agent grafted polyester fiber, the molar ratio of amino group on the surface of the modified polyester fiber: RAFT agent: catalyst: dehydrating agent is 0.02:1:2:0.25;
[0027] Further, the catalyst includes EDC hydrochloride;
[0028] Further, the dehydrating agent includes 4-dimethylaminopyridine;
[0029] Furthermore, the vacuum pressure is ≤-80 kPa, and the nitrogen filling time is 30-60 s;
[0030] Further, the RAFT agent includes 4-cyano-4-[(dodecylsulfanylsulfanylcarbonyl)sulfanyl]pentanoic acid;
[0031] S7: Add RAFT agent to N, N-dimethylformamide, stir evenly, add methacrylate glycidyl ether and photocatalyst, stir evenly, add RAFT agent to graft polyester fiber, react under nitrogen atmosphere at room temperature for 24 hours, take out the polyester fiber, wash with N, N-dimethylformamide and ethanol alternately, and vacuum dry at 50°C for 12 hours to obtain methacrylate glycidyl ether grafted polyester fiber;
[0032] Furthermore, in the preparation process of the glycidyl methacrylate grafted polyester fiber, the molar ratio of glycidyl methacrylate: RAFT agent: RAFT agent grafted polyester fiber surface RAFT agent: photocatalyst is 600:2:1:0.6, 600:2:1:0.12;
[0033] Further, the photocatalyst includes ZnTPP;
[0034] Furthermore, the illumination intensity of the illumination reaction includes 4.0W / m 2 ;
[0035] S8: adding a dimethyl sulfoxide solution of an anti-ultraviolet agent and a dimethyl sulfoxide solution of acetylacetonate iron (III) to a reaction container, adding methacrylate glycidyl ether grafted polyester fiber, injecting the dimethyl sulfoxide solution of acetylacetonate iron (III) again under a nitrogen atmosphere, performing vacuuming and nitrogen filling treatments for three times, heating to 90-92° C. for reaction for 6-6.5 hours, taking out the polyester fiber, washing with ethanol, and vacuum drying at 50° C. for 12 hours to obtain a highly flame-retardant polyester fiber;
[0036] Furthermore, in the preparation process of the highly flame-retardant polyester fiber, the molar ratio of epoxy group grafted on the polyester fiber surface by glycidyl methacrylate: anti-ultraviolet agent: iron (III) acetylacetonate is 4:1:0.02;
[0037] Furthermore, the anti-ultraviolet agent includes 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention prepares a copolyester with flame retardancy and anti-drip properties by in-situ polymerization of a phosphorus-containing flame retardant and acidic silica. Different from the traditional method of adding flame retardants to polyester for blending, the present invention prepares polyester fibers with excellent flame retardancy and flame retardants that are not easy to migrate. The formation of a dense carbon layer during combustion is enhanced by acidic silica sol, and the acidic silica sol can also inhibit the expansion of residual carbon by forming holes, further improving the flame retardant properties of polyester fibers. The phosphorus-containing flame retardant group and the acidic silicon solvent form a synergistic cross-linking structure to achieve anti-drip properties, thereby achieving flame retardancy and anti-drip effects, solving the problem that conventional anti-drip methods reduce flame retardancy and may bring more smoke.
[0040] 2. The mussel-inspired method of the present invention based on homemade polyester fiber can be used as a surface treatment to enhance the material to effectively improve the mechanical properties of the material. The catechol and polyethyleneimine are co-deposited on the polyester fiber. On the one hand, it can enhance the mechanical properties of the material, and on the other hand, it provides a large number of active sites for the subsequent grafting of anti-ultraviolet agents through RAFT agents. On this basis, the present invention further grafts the RAFT agent on the surface of the modified polyester fiber, controls the growth of glycidyl methacrylate on the polyester fabric through the SI-PET-RAFT method, and finally, grafts the benzotriazole anti-ultraviolet agent as a secondary functionalization to prepare a polyester fiber with excellent water resistance, UV resistance, and high flame retardancy. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] In the following examples, [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid CAS: 63562-33-4; branched polyethyleneimine molecular weight: 600, purchased from Aladdin; 4-cyano-4-[(dodecylsulfanylsulfanyl)sulfanyl]pentanoic acid CAS: 870196-80-8; ZnTPPCAS: 14074-80-7; 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid CAS: 84268-36-0; and the remaining raw materials are commercially available.
[0043] In the following embodiments, the method for preparing polyester fiber comprises the following steps:
[0044] S1: 0.8 mL of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]butanedioic acid and 2 mL of ethylene glycol were added to a reaction vessel, stirred evenly, heated to 180° C. for reaction for 6 h under a nitrogen atmosphere, and further heated to 195° C. to remove ethylene glycol and water to obtain a flame retardant diol compound;
[0045] S2: 50 mL of ethylene glycol, 55 mL of deionized water, and 1 mL of phosphoric acid were added to the reaction container in sequence, the pH of the phosphoric acid was adjusted to 2.0, 100 mL of tetraethyl orthosilicate was added, and the mixture was stirred evenly. 1 mL of silane coupling agent KH560 was added, and the mixture was kept warm for 4 h. The ethanol and water were removed by distillation under reduced pressure to obtain a nano-silica sol;
[0046] S3: 1.3 mol of terephthalic acid and 0.05 mol of ethylene glycol are added to a reaction container, and the reaction is preheated to 230°C for esterification reaction. When the amount of water reaches the theoretical value, 1 mol of flame retardant diol compound and 1 wt% of nano silica sol are added, and 0.01 mol of ethylene glycol antimony is added. The reaction system is placed at 250°C and 300 Pa vacuum for 60 minutes, and further heated to 270°C for 2 hours. The reaction product is placed at 120°C for pre-crystallization treatment for 3 hours, dried, and cooled to room temperature to obtain polyester;
[0047] S4: Spinning and stretching the polyester to obtain polyester fibers.
[0048] Example 1: A method for preparing highly flame-retardant polyester fiber for protective gloves: Step (1): placing the polyester fiber in a reaction container, adding 1 mL of an ethanol solution of catechol with a concentration of 1 mg / mL and 0.5 mL of a Tris buffer solution of branched polyethyleneimine with a concentration of 0.5 mg / mL, and reacting at room temperature with shaking for 24 hours, taking out the polyester fiber, washing it alternately with deionized water and ethanol, and vacuum drying it at 60° C. for 24 hours to obtain a modified polyester fiber;
[0049] Step (2): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, EDC hydrochloride and 4-dimethylaminopyridine to N,N-dimethylformamide respectively, stirring evenly to obtain solution A, solution B and solution C; adding solution B and solution A to a reaction vessel, stirring evenly, adding modified polyester fiber, sealing, vacuumizing and nitrogen filling treatment 3 times, injecting solution A into the reaction vessel, vacuumizing and nitrogen filling treatment 3 times, heating to 40°C for reaction for 24 hours, taking out the polyester fiber, washing it with N,N-dimethylformamide and ethanol alternately, and vacuum drying it at 50°C for 12 hours to obtain RAFT agent grafted polyester fiber;
[0050] In the preparation process of the RAFT agent grafted polyester fiber, the molar ratio of amino groups on the surface of the modified polyester fiber: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: EDC hydrochloride: 4-dimethylaminopyridine is 0.02:1:2:0.25;
[0051] Step (3): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid to N,N-dimethylformamide, stirring evenly, adding methyl methacrylate glycidyl ether and ZnTPP, stirring evenly, adding RAFT agent to graft polyester fiber, reacting under nitrogen atmosphere at room temperature for 24 hours, taking out the polyester fiber, washing with N,N-dimethylformamide and ethanol alternately, and vacuum drying at 50° C. for 12 hours to obtain methyl methacrylate glycidyl ether grafted polyester fiber;
[0052] In the preparation process of the methacrylate glycidyl ether grafted polyester fiber, the molar ratio of methacrylate glycidyl ether: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: RAFT agent grafted polyester fiber surface RAFT agent: ZnTPP is 600:2:1:0.6;
[0053] Step (4): adding a dimethyl sulfoxide solution of 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid and a dimethyl sulfoxide solution of acetylacetonate iron (III) to a reaction container, adding methacrylate glycidyl ether grafted polyester fiber, injecting the dimethyl sulfoxide solution of acetylacetonate iron (III) again under a nitrogen atmosphere, performing vacuuming and nitrogen filling treatment three times, heating to 90° C. for reaction for 6 h, taking out the polyester fiber, washing with ethanol, and vacuum drying at 50° C. for 12 h to obtain a highly flame-retardant polyester fiber;
[0054] In the preparation process of the highly flame-retardant polyester fiber, the molar ratio of methacrylate glycidyl ether grafted onto the epoxy group on the polyester fiber surface: 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid: acetylacetonate iron (III) is 4:1:0.02.
[0055] Embodiment 2: A method for preparing highly flame-retardant polyester fiber for protective gloves: The method for preparing polyester fiber comprises the following steps:
[0056] S1: 0.8 mL of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]butanedioic acid and 2 mL of ethylene glycol were added to a reaction vessel, stirred evenly, heated to 180° C. for reaction for 6 h under a nitrogen atmosphere, and further heated to 195° C. to remove ethylene glycol and water to obtain a flame retardant diol compound;
[0057] S2: 50 mL of ethylene glycol, 55 mL of deionized water, and 1 mL of phosphoric acid were added to the reaction container in sequence, the pH of the phosphoric acid was adjusted to 2.0, 100 mL of tetraethyl orthosilicate was added, and the mixture was stirred evenly. 1 mL of silane coupling agent KH560 was added, and the mixture was kept warm for 4 h. The ethanol and water were removed by distillation under reduced pressure to obtain a nano-silica sol;
[0058] S3: 1.3 mol of terephthalic acid and 0.05 mol of ethylene glycol are added to a reaction container, and the reaction is preheated to 230°C for esterification reaction. When the amount of water reaches the theoretical value, 1 mol of flame retardant diol compound and 2 wt% of nano silica sol are added, and 0.01 mol of ethylene glycol antimony is added. The reaction system is placed at 250°C and 300 Pa vacuum for 60 minutes, and further heated to 270°C for 2 hours. The reaction product is placed at 120°C for pre-crystallization treatment for 3 hours, dried, and cooled to room temperature to obtain polyester;
[0059] S4: Spinning and stretching the polyester to obtain polyester fibers.
[0060] The remaining steps are the same as those in Example 1.
[0061] Embodiment 3: A method for preparing highly flame-retardant polyester fiber for protective gloves: The method for preparing polyester fiber comprises the following steps:
[0062] S1: 0.8 mL of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]butanedioic acid and 2 mL of ethylene glycol were added to a reaction vessel, stirred evenly, heated to 180° C. for reaction for 6 h under a nitrogen atmosphere, and further heated to 195° C. to remove ethylene glycol and water to obtain a flame retardant diol compound;
[0063] S2: 50 mL of ethylene glycol, 55 mL of deionized water, and 1 mL of phosphoric acid were added to the reaction container in sequence, the pH of the phosphoric acid was adjusted to 2.0, 100 mL of tetraethyl orthosilicate was added, and the mixture was stirred evenly. 1 mL of silane coupling agent KH560 was added, and the mixture was kept warm for 4 h. The ethanol and water were removed by distillation under reduced pressure to obtain a nano-silica sol;
[0064] S3: 1.3 mol of terephthalic acid and 0.05 mol of ethylene glycol are added to a reaction container, and the reaction is preheated to 230°C for esterification reaction. When the amount of water reaches the theoretical value, 1 mol of flame retardant diol compound and 3 wt% of nano silica sol are added, and 0.01 mol of ethylene glycol antimony is added. The reaction system is placed at 250°C and 300 Pa vacuum for 60 minutes, and further heated to 270°C for 2 hours. The reaction product is placed at 120°C for pre-crystallization treatment for 3 hours, dried, and cooled to room temperature to obtain polyester;
[0065] S4: Spinning and stretching the polyester to obtain polyester fibers.
[0066] The remaining steps are the same as those in Example 1.
[0067] Example 4: A method for preparing highly flame-retardant polyester fiber for protective gloves: Step (1): placing the polyester fiber in a reaction container, adding 1 mL of an ethanol solution of catechol with a concentration of 1 mg / mL and 0.5 mL of a Tris buffer solution of branched polyethyleneimine with a concentration of 1 mg / mL, and reacting at room temperature with shaking for 24 hours, taking out the polyester fiber, washing it alternately with deionized water and ethanol, and vacuum drying it at 60°C for 24 hours to obtain a modified polyester fiber;
[0068] Step (2): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, EDC hydrochloride and 4-dimethylaminopyridine to N,N-dimethylformamide respectively, stirring evenly to obtain solution A, solution B and solution C; adding solution B and solution A to a reaction vessel, stirring evenly, adding modified polyester fiber, sealing, vacuumizing and nitrogen filling treatment 3 times, injecting solution A into the reaction vessel, vacuumizing and nitrogen filling treatment 3 times, heating to 40°C for reaction for 24 hours, taking out the polyester fiber, washing it with N,N-dimethylformamide and ethanol alternately, and vacuum drying it at 50°C for 12 hours to obtain RAFT agent grafted polyester fiber;
[0069] In the preparation process of the RAFT agent grafted polyester fiber, the molar ratio of amino groups on the surface of the modified polyester fiber: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: EDC hydrochloride: 4-dimethylaminopyridine is 0.02:1:2:0.25;
[0070] Step (3): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid to N,N-dimethylformamide, stirring evenly, adding methyl methacrylate glycidyl ether and ZnTPP, stirring evenly, adding RAFT agent to graft polyester fiber, reacting under nitrogen atmosphere at room temperature for 24 hours, taking out the polyester fiber, washing with N,N-dimethylformamide and ethanol alternately, and vacuum drying at 50° C. for 12 hours to obtain methyl methacrylate glycidyl ether grafted polyester fiber;
[0071] In the preparation process of the methacrylate glycidyl ether grafted polyester fiber, the molar ratio of methacrylate glycidyl ether: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: RAFT agent grafted polyester fiber surface RAFT agent: ZnTPP is 600:2:1:0.6;
[0072] Step (4): adding a dimethyl sulfoxide solution of 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid and a dimethyl sulfoxide solution of acetylacetonate iron (III) to a reaction container, adding methacrylate glycidyl ether grafted polyester fiber, injecting the dimethyl sulfoxide solution of acetylacetonate iron (III) again under a nitrogen atmosphere, performing vacuuming and nitrogen filling treatment three times, heating to 90° C. for reaction for 6 h, taking out the polyester fiber, washing with ethanol, and vacuum drying at 50° C. for 12 h to obtain a highly flame-retardant polyester fiber;
[0073] In the preparation process of the highly flame-retardant polyester fiber, the molar ratio of methacrylate glycidyl ether grafted onto the epoxy group on the polyester fiber surface: 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid: iron (III) acetylacetonate is 4:1:0.02.
[0074] The remaining steps are the same as those in Example 2.
[0075] Example 5: A method for preparing highly flame-retardant polyester fiber for protective gloves: Step (1): placing the polyester fiber in a reaction container, adding 1 mL of an ethanol solution of catechol with a concentration of 1 mg / mL and 0.5 mL of a Tris buffer solution of branched polyethyleneimine with a concentration of 2 mg / mL, and reacting at room temperature with shaking for 24 hours, taking out the polyester fiber, washing it alternately with deionized water and ethanol, and vacuum drying it at 60°C for 24 hours to obtain a modified polyester fiber;
[0076] Step (2): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, EDC hydrochloride and 4-dimethylaminopyridine to N,N-dimethylformamide respectively, stirring evenly to obtain solution A, solution B and solution C; adding solution B and solution A to a reaction vessel, stirring evenly, adding modified polyester fiber, sealing, vacuumizing and nitrogen filling treatment 3 times, injecting solution A into the reaction vessel, vacuumizing and nitrogen filling treatment 3 times, heating to 40°C for reaction for 24 hours, taking out the polyester fiber, washing it with N,N-dimethylformamide and ethanol alternately, and vacuum drying it at 50°C for 12 hours to obtain RAFT agent grafted polyester fiber;
[0077] In the preparation process of the RAFT agent grafted polyester fiber, the molar ratio of amino groups on the surface of the modified polyester fiber: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: EDC hydrochloride: 4-dimethylaminopyridine is 0.02:1:2:0.25;
[0078] Step (3): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid to N,N-dimethylformamide, stirring evenly, adding methyl methacrylate glycidyl ether and ZnTPP, stirring evenly, adding RAFT agent to graft polyester fiber, reacting under nitrogen atmosphere at room temperature for 24 hours, taking out the polyester fiber, washing with N,N-dimethylformamide and ethanol alternately, and vacuum drying at 50° C. for 12 hours to obtain methyl methacrylate glycidyl ether grafted polyester fiber;
[0079] In the preparation process of the methacrylate glycidyl ether grafted polyester fiber, the molar ratio of methacrylate glycidyl ether: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: RAFT agent grafted polyester fiber surface RAFT agent: ZnTPP is 600:2:1:0.6;
[0080] Step (4): adding a dimethyl sulfoxide solution of 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid and a dimethyl sulfoxide solution of acetylacetonate iron (III) to a reaction container, adding methacrylate glycidyl ether grafted polyester fiber, injecting the dimethyl sulfoxide solution of acetylacetonate iron (III) again under a nitrogen atmosphere, performing vacuuming and nitrogen filling treatment three times, heating to 90° C. for reaction for 6 h, taking out the polyester fiber, washing with ethanol, and vacuum drying at 50° C. for 12 h to obtain a highly flame-retardant polyester fiber;
[0081] In the preparation process of the highly flame-retardant polyester fiber, the molar ratio of methacrylate glycidyl ether grafted onto the epoxy group on the polyester fiber surface: 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid: iron (III) acetylacetonate is 4:1:0.02.
[0082] The remaining steps are the same as those in Example 2.
[0083] Comparative Example 1: A method for preparing highly flame-retardant polyester fiber for protective gloves: A method for preparing polyester fiber, comprising the following steps: S1: adding 0.8 mL [(6-oxo-6H-dibenzo [C, E] [1, 2] oxaphosphorin-6-yl) methyl] butanedioic acid and 2 mL ethylene glycol to a reaction container, stirring evenly, heating to 180° C. for reaction for 6 h under a nitrogen atmosphere, and further heating to 195° C. to remove ethylene glycol and water to obtain a flame retardant diol compound;
[0084] S2: 50 mL of ethylene glycol, 55 mL of deionized water, and 1 mL of phosphoric acid were added to the reaction container in sequence, the pH of the phosphoric acid was adjusted to 2.0, 100 mL of tetraethyl orthosilicate was added, and the mixture was stirred evenly. 1 mL of silane coupling agent KH560 was added, and the mixture was kept warm for 4 h. The ethanol and water were removed by distillation under reduced pressure to obtain a nano-silica sol;
[0085] S3: 1.3 mol of terephthalic acid and 0.05 mol of ethylene glycol are added to a reaction vessel, and the reaction is preheated to 230°C for esterification reaction. When the amount of water reaches the theoretical value, 1 mol of flame retardant diol compound and 0.01 mol of ethylene glycol antimony are added. The reaction system is placed at 250°C and 300 Pa vacuum for 60 min, and further heated to 270°C for 2 h. The reaction product is placed at 120°C for pre-crystallization treatment for 3 h, dried, and cooled to room temperature to obtain polyester.
[0086] S4: Spinning and stretching the polyester to obtain polyester fibers.
[0087] The remaining steps are the same as those in Example 1.
[0088] Comparative Example 2: A method for preparing highly flame-retardant polyester fiber for protective gloves: The method for preparing polyester fiber comprises the following steps:
[0089] S1: 0.8 mL of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]butanedioic acid and 2 mL of ethylene glycol were added to a reaction vessel, stirred evenly, heated to 180° C. for reaction for 6 h under a nitrogen atmosphere, and further heated to 195° C. to remove ethylene glycol and water to obtain a flame retardant diol compound;
[0090] S2: 50 mL of ethylene glycol, 55 mL of deionized water, and 1 mL of phosphoric acid were added to the reaction container in sequence, the pH of the phosphoric acid was adjusted to 2.0, 100 mL of tetraethyl orthosilicate was added, and the mixture was stirred evenly. 1 mL of silane coupling agent KH560 was added, and the mixture was kept warm for 4 h. The ethanol and water were removed by distillation under reduced pressure to obtain a nano-silica sol;
[0091] S3: 1.3 mol of terephthalic acid and 0.05 mol of ethylene glycol are added to a reaction container, and the reaction is preheated to 230°C for esterification reaction. When the amount of water reaches the theoretical value, 1 mol of flame retardant diol compound and 4 wt% of nano silica sol are added, and 0.01 mol of ethylene glycol antimony is added. The reaction system is placed at 250°C and 300 Pa vacuum for 60 minutes, and further heated to 270°C for 2 hours. The reaction product is placed at 120°C for pre-crystallization treatment for 3 hours, dried, and cooled to room temperature to obtain polyester;
[0092] S4: Spinning and stretching the polyester to obtain polyester fibers.
[0093] Comparative Example 3: A method for preparing highly flame-retardant polyester fiber for protective gloves: Step (1): placing the polyester fiber in a reaction container, adding 1 mL of an ethanol solution of catechol with a concentration of 1 mg / mL and 0.5 mL of a Tris buffer solution of branched polyethyleneimine with a concentration of 3 mg / mL, and reacting at room temperature with shaking for 24 hours, taking out the polyester fiber, washing it alternately with deionized water and ethanol, and vacuum drying it at 60° C. for 24 hours to obtain a modified polyester fiber;
[0094] Step (2): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, EDC hydrochloride and 4-dimethylaminopyridine to N,N-dimethylformamide respectively, stirring evenly to obtain solution A, solution B and solution C; adding solution B and solution A to a reaction vessel, stirring evenly, adding modified polyester fiber, sealing, vacuumizing and nitrogen filling treatment 3 times, injecting solution A into the reaction vessel, vacuumizing and nitrogen filling treatment 3 times, heating to 40°C for reaction for 24 hours, taking out the polyester fiber, washing it with N,N-dimethylformamide and ethanol alternately, and vacuum drying it at 50°C for 12 hours to obtain RAFT agent grafted polyester fiber;
[0095] In the preparation process of the RAFT agent grafted polyester fiber, the molar ratio of amino groups on the surface of the modified polyester fiber: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: EDC hydrochloride: 4-dimethylaminopyridine is 0.02:1:2:0.25;
[0096] Step (3): adding 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid to N,N-dimethylformamide, stirring evenly, adding methyl methacrylate glycidyl ether and ZnTPP, stirring evenly, adding RAFT agent to graft polyester fiber, reacting under nitrogen atmosphere at room temperature for 24 hours, taking out the polyester fiber, washing with N,N-dimethylformamide and ethanol alternately, and vacuum drying at 50° C. for 12 hours to obtain methyl methacrylate glycidyl ether grafted polyester fiber;
[0097] In the preparation process of the methacrylate glycidyl ether grafted polyester fiber, the molar ratio of methacrylate glycidyl ether: 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid: RAFT agent grafted polyester fiber surface RAFT agent: ZnTPP is 600:2:1:0.6;
[0098] Step (4): adding a dimethyl sulfoxide solution of 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid and a dimethyl sulfoxide solution of acetylacetonate iron (III) to a reaction container, adding methacrylate glycidyl ether grafted polyester fiber, injecting the dimethyl sulfoxide solution of acetylacetonate iron (III) again under a nitrogen atmosphere, performing vacuuming and nitrogen filling treatment three times, heating to 90° C. for reaction for 6 h, taking out the polyester fiber, washing with ethanol, and vacuum drying at 50° C. for 12 h to obtain a highly flame-retardant polyester fiber;
[0099] In the preparation process of the highly flame-retardant polyester fiber, the molar ratio of methacrylate glycidyl ether grafted onto the epoxy group on the polyester fiber surface: 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid: iron (III) acetylacetonate is 4:1:0.02.
[0100] The remaining steps are the same as those in Example 1.
[0101] Comparative Example 4: A method for preparing highly flame-retardant polyester fiber for protective gloves: The polyester fiber is immersed in a dimethyl sulfoxide solution of 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylbenzenepropionic acid, the polyester fiber is taken out, washed with ethanol, and vacuum dried at 50°C for 12 hours to obtain a highly flame-retardant polyester fiber.
[0102] Experiment: The highly flame-retardant polyester fibers prepared in the above examples and comparative examples were prepared into polyester plain weave fabric samples with a gram weight of 130 g / m 2 The average diameter of the fiber bundle is 0.5mm.
[0103] Limiting oxygen index test: Cut the sample into 150mm×58mm and test it according to GB / T 5455-2014. Cut the sample into 150mm×58mm, and after accelerated aging by ultraviolet radiation, conduct limiting oxygen index test again. Ultraviolet radiation parameters include: Light source: 500W high pressure mercury lamp, 365nm ultraviolet light density: 16.8W / m 2 , temperature is 40°C, and the distance between the light source and the sample is 37 cm.
[0104] UL-94 test: Cut the sample into 300mm×89mm and test according to GB / T 5455-2014.
[0105] Ultraviolet transmittance: The fabric was washed three times and then dried. The UV-Vis absorption characteristics of the fabric were measured using a spectrophotometer in the wavelength range of 200-600nm. The average absorbance in the range of 280-400nm was taken as the characterization data of the fabric's anti-ultraviolet performance.
[0106] The experimental data are shown in Table 1 below.
[0107] Table 1 High flame retardant polyester fiber experimental data table
[0108] LOI / % LOI (after aging) / % UL-94 UV transmittance / % Example 1 32.6 30.9 V-0 2.77 Example 2 36.7 34.9 V-0 2.80 Example 3 34.1 32.4 V-0 2.78 Example 4 36.5 35.9 V-0 2.09 Example 5 36.6 35.5 V-0 2.47 Comparative Example 1 30.3 28.7 V-1 2.75 Comparative Example 3 32.5 28.7 V-0 3.66 Comparative Example 4 32.6 25.4 V-0 5.12
[0109] Conclusion: The highly flame-retardant polyester fiber prepared by the present invention has excellent flame retardancy and UV resistance.
[0110] In the process of preparing polyester fiber in Comparative Example 1, no nano-silica sol was added, resulting in decreased flame retardancy and anti-dripping properties of the polyester fiber.
[0111] In comparative example 2, excessive nano-silica sol was added during the preparation of polyester fiber. The network acidic silica sol made the copolyester difficult to spin, so the scheme was abandoned without specific experimental data.
[0112] In Comparative Example 3, excessive branched polyethyleneimine is added during the preparation of modified polyester fiber. This is mainly because excessive polyethyleneimine will prevent the covalent bonding between aromatic rings and the π-π stacking of catechol during the oxidation process, thereby inhibiting the formation of co-deposition aggregates, resulting in a reduction in active sites during the subsequent grafting of anti-UV agents and a decrease in anti-aging performance.
[0113] In Comparative Example 4, the polyester fiber is loaded with the anti-ultraviolet agent by direct impregnation, which is easy to fall off, resulting in a reduction in the service life of the polyester fiber.
[0114] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing highly flame-retardant polyester fiber for protective gloves, characterized in that: Add a dimethyl sulfoxide solution of an anti-ultraviolet agent and a dimethyl sulfoxide solution of ferric acetylacetonate into a reaction container, add methacrylate glycidyl ether grafted polyester fiber, inject the dimethyl sulfoxide solution of ferric acetylacetonate again under a nitrogen atmosphere, perform vacuuming and nitrogen filling treatment, heat to 90-92° C. and react for 6-6.5 hours, take out the polyester fiber, wash it, and vacuum dry it to obtain a highly flame-retardant polyester fiber.
2. The method for preparing a highly flame-retardant polyester fiber for protective gloves according to claim 1, characterized in that: In the preparation process of highly flame-retardant polyester fiber, the molar ratio of epoxy group grafted on the polyester fiber surface by glycidyl methacrylate: anti-ultraviolet agent: ferric acetylacetonate is 4:1:0.
02.
3. The method for preparing a highly flame-retardant polyester fiber for protective gloves according to claim 1, characterized in that: The preparation method of methacrylate glycidyl ether grafted polyester fiber comprises the following steps: adding RAFT agent to N, N-dimethylformamide, stirring evenly, adding methacrylate glycidyl ether and photocatalyst, stirring evenly, adding RAFT agent to graft polyester fiber, reacting with light at room temperature for 24 hours under nitrogen atmosphere, taking out the polyester fiber, washing, and vacuum drying to obtain methacrylate glycidyl ether grafted polyester fiber.
4. The method for preparing a highly flame-retardant polyester fiber for protective gloves according to claim 3, characterized in that: In the preparation process of methacrylate glycidyl ether grafted polyester fiber, the molar ratio of methacrylate glycidyl ether: RAFT agent: RAFT agent grafted polyester fiber surface RAFT agent: photocatalyst is 600:2:1:0.6, 600:2:1:0.
12.
5. The method for preparing highly flame-retardant polyester fiber for protective gloves according to claim 3, characterized in that: The preparation method of RAFT agent grafted polyester fiber comprises the following steps: adding RAFT agent, catalyst and dehydrating agent to N, N-dimethylformamide respectively, stirring evenly to obtain solution A, solution B and solution C; adding solution B and solution A to a reaction container, stirring evenly, adding modified polyester fiber, sealing, vacuumizing and nitrogen filling treatment for 3 times, injecting solution A into the reaction container, vacuumizing and nitrogen filling treatment for 3 times, heating to 40-42°C for reaction for 24 hours, taking out the polyester fiber, washing with N, N-dimethylformamide and ethanol alternately, and vacuum drying at 50°C for 12 hours to obtain RAFT agent grafted polyester fiber.
6. The method for preparing highly flame-retardant polyester fiber for protective gloves according to claim 5, characterized in that: In the preparation process of RAFT agent grafted polyester fiber, the molar ratio of amino group on the surface of modified polyester fiber: RAFT agent: catalyst: dehydrating agent is 0.02:1:2:0.
25.
7. The method for preparing highly flame-retardant polyester fiber for protective gloves according to claim 5, characterized in that: Preparation process of modified polyester fiber The method comprises the following steps: placing polyester fiber in a reaction container, adding an ethanol solution of catechol and a Tris buffer solution of branched polyethyleneimine, performing an oscillation reaction at room temperature for 24 hours, taking out the polyester fiber, washing it alternately with deionized water and ethanol, and vacuum drying it at 60°C for 24 hours to obtain the modified polyester fiber.
8. The method for preparing highly flame-retardant polyester fiber for protective gloves according to claim 7, characterized in that: In the preparation process of the modified polyester fiber, the volume ratio of the ethanol solution of catechol to the Tris buffer solution of the branched polyethyleneimine is 1:(0.5-2).
9. The method for preparing highly flame-retardant polyester fiber for protective gloves according to claim 7, characterized in that: Preparation method of polyester fiber, The following steps are involved: S1: Add dicarboxylic acid flame retardant and ethylene glycol into a reaction container, stir evenly, heat to 180-185°C under nitrogen atmosphere for reaction for 6-6.5h, and further heat to 195°C to remove ethylene glycol and water to obtain a flame retardant diol compound; In the preparation process of the dicarboxylic acid flame retardant glycol compound, the volume ratio of dicarboxylic acid flame retardant: ethylene glycol is (0.8-1): (2-2.4); S2: Ethylene glycol, deionized water and phosphoric acid are added to the reaction container in sequence, the pH is adjusted to 2.0-2.1, tetraethyl orthosilicate is added, stirred evenly, silane coupling agent KH560 is added, the reaction is kept warm for 4-4.5 hours, and ethanol and water are removed by vacuum distillation to obtain nano-silica sol; In the preparation process of nano-silica sol, the volume ratio of phosphoric acid:ethyl orthosilicate:silane coupling agent KH560 is 1:100:1; S3: Add terephthalic acid and ethylene glycol to a reaction vessel, preheat to 230°C for esterification reaction, add flame retardant diol compound, nano silica sol, and ethylene glycol antimony when the water content reaches the theoretical value, place the reaction system at 250-260°C and 300Pa vacuum, react for 60-65min, further heat to 270-275°C for reaction for 2-2.5h, place the reaction product at 120-140°C for pre-crystallization treatment, dry, and cool to room temperature to obtain polyester; In the process of preparing polyester, the molar ratio of terephthalic acid: ethylene glycol: flame retardant diol compound is (1.3-1.35): (0.05-0.1): 1; the amount of nano-silica sol added is 1-3wt% of the total mass of terephthalic acid, ethylene glycol, and flame retardant diol compound; S4: Spinning and stretching the polyester to obtain polyester fibers.
10. The highly flame-retardant polyester fiber prepared according to the method for preparing highly flame-retardant polyester fiber for protective gloves according to any one of claims 1 to 9.
